Corrigendum to "Delaunay Hodge star" [Comput. Aided Des. 45 (2013) 540–544]. (March 2018) - Hirani, Anil N.; Kalyanaraman, Kaushik; VanderZee, Evan B.
Abstract: A discrete diagonal Hodge star operator for pairwise Delaunay triangulations was described in Hirani et al. (2013). This note fixes errors in two figures and some indexing mistakes in the original paper. One consequence of this fix is that discrete exterior calculus may be applicable to a wider class of meshes.